Effectiveness of an educational program on nurse’s knowledge concerning danger of mixing Medications in Al- Hussein Teaching Hospital in Al-Muthana Governorate - Mahmood, Ahmed Harbi; Hassan, Huda Baqar (International Journal of Psychosocial Rehabilitation, 2020)
Mixing treatments is defined as the process of mixing two or more treatments before, during, or after giving together, or one treatment with food or herbs etc, and it is either directly as mixing two treatments in one syringe, or indirectly as in taking two treatments at the same time orally. Mixing medication from unhealthy habits that are widespread in the country, and some may have become addicted to believing that they benefit or are more effective than if the treatments were separate.